ASPEK KEPRIBADIAN TOKOH UTAMA DALAM CERPEN CERITA PENDEK YANG PANJANG KARYA HASTA INDRIYANA, KAJIAN PSIKOLOGI SASTRA, DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR SASTRA DI SMA - Naidi Pertiwi Rahayu; Rizki Sri Lestari; Citra Anjani; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This research done with the aim to describe the background socio historical author, describe the structure build a short story, describe the personality of the main character in the short story, and describe the implementation of the value of personality of the main character in the short story cerita pendek yang panjang as a teaching materials literature in high school. Research and research strategy this is a descriptive qualitative and case studies estabilished. Based on data analysis can be obtained as follows : background sosio historical story writer cerita pendek yang panjang, Hasta Indriyana is a writer from Gunungkidul, which has formulate the work of fiction and nonfiction and in a collection of the book together. The short story cerita pendek yang panjang, the main character is “Me”. Flow used in the short story this is a flow mixture. Background time in the short story is the case when the morning and afternoon while the background place of occurance is in a red light intersection three. Aspect of personalityin the short storythis includes the personality types of people wo empathyand the results of the motivation life can be implemented in the study level high school / MA class XI/I competence reading skills, the standard competence understand the elements of intrinsik nd extrinsic short stories Indonesian or translation.